Displacement after the Camp Fire: Where are the Most Vulnerable?. Issue 12 (2nd December 2021) - Chase, Jacquelyn; Hansen, Peter
Abstract: Recovery from wildfire is often cast as the rebuilding of homes by the displaced. This focus ignores the diversity of livelihoods and access to resources among people living in the wildland-urban interface. The 2018 Camp Fire in Butte County, northern California, invites the rethinking of vulnerability and wildfire. Almost an entire town of 27, 000 was destroyed, as well as long-established surrounding rural communities. The extent of devastation and displacement has revealed the shortcoming of a perspective of victimhood that focuses on property ownership. We challenge this bias that equates community with property ownership with three sources of data that, although limited, allow for a more granular view of the diversity of displacement and the ongoing vulnerability that exists in the shadows of the rebuild.